2019
DOI: 10.1161/jaha.119.013212
|View full text |Cite
|
Sign up to set email alerts
|

Gait Speed and Mood, Cognition, and Quality of Life in Older Adults With Atrial Fibrillation

Abstract: BackgroundLow gait speed has been linked with impaired mood, cognition, and quality of life (QOL) in older adults. We examined whether low gait speed was associated with impaired mood, cognition, and QOL among older adults with atrial fibrillation (AF).Methods and ResultsParticipants (n=1185) had a diagnosis of AF, aged ≥65 years, CHA 2 DS 2 VASc ≥2 and had no contraindications to anticoagulation. Participants completed a 15‐foot walk test, and low gait speed was categorized using cutoffs from the Fried Frailt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Considering the specificity of our cohort, that is, elderly AF patients, our results were in line with those of the only study that showed a direct association between gait and cognition in this population (20). Marino and colleagues found that, among the 1,185 AF participants aged ≥65 years, those with low gait speed were significantly more likely to have cognitive impairment independently from several demographic and clinical characteristics.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Considering the specificity of our cohort, that is, elderly AF patients, our results were in line with those of the only study that showed a direct association between gait and cognition in this population (20). Marino and colleagues found that, among the 1,185 AF participants aged ≥65 years, those with low gait speed were significantly more likely to have cognitive impairment independently from several demographic and clinical characteristics.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, preliminary data are emerging also on the association between AF and reduced mobility in older adults independently of comorbidities and frailty markers (17)(18)(19). Only one recent study by Marino and colleagues directly assessed the association between a reduced gait speed and the presence of cognitive impairment in a population of elderly patients with AF (20). Their results confirmed such association independently from several demographic and clinical characteristics, and the authors concluded that physical changes in gait could be related to declines in the cognitive domains that regulate several gait elements as previously documented in literature on neurologic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We used baseline data from the prospective multi-center study entitled "Systematic Assessment of Geriatric Elements in AF (SAGE-AF)". Details of participant recruitment and study protocols have been described previously [18][19][20]. Participants were recruited from three medical centers in Massachusetts and two medical centers in Central Georgia between 2015 and 2018.…”
Section: Study Populationmentioning
confidence: 99%
“…Patients with AF had low gait speed, and low gait speed has been linked with impaired mood, cognition, and quality of life. 21 The presence of AF influences negatively the quality of life, as it remains symptomatic in about twothirds of patients despite them receiving medical treatment. 22 Previous studies investigating the impact of AF on HRQoL found poorer HRQoL in AF patients compared to the general population.…”
Section: Introductionmentioning
confidence: 99%